2019
DOI: 10.1186/s12882-019-1450-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dialysate potassium and lactate on serum potassium and bicarbonate concentrations during daily hemodialysis at low dialysate flow rates

Abstract: Background Observational studies of hemodialysis patients treated thrice weekly have shown that serum and dialysate potassium and bicarbonate concentrations are associated with patient outcomes. The effect of more frequent hemodialysis on serum potassium and bicarbonate concentrations has rarely been studied, especially for treatments at low dialysate flow rate. Methods These post-hoc analyses evaluated data from patients who transferred from in-center hemodialysis (HD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…We recently demonstrated that the dialysate concentration of lactate can influence predialysis serum tCO 2 concentrations when patients are transferred from ICHD to daily home HD using the NxStage System One during the FREEDOM study 2 ; however, the treatments prescribed during that study were restricted to almost universally 20 to 25 L of dialysate volume for six treatments per week. Those findings, while noteworthy, may not be generalizable to today as current FHD treatment prescriptions are highly varied in clinical practice (internal data from NxStage Medical).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that the dialysate concentration of lactate can influence predialysis serum tCO 2 concentrations when patients are transferred from ICHD to daily home HD using the NxStage System One during the FREEDOM study 2 ; however, the treatments prescribed during that study were restricted to almost universally 20 to 25 L of dialysate volume for six treatments per week. Those findings, while noteworthy, may not be generalizable to today as current FHD treatment prescriptions are highly varied in clinical practice (internal data from NxStage Medical).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data analyzed in this study were collected during the FREEDOM study and were previously reported 2 . Predialysis serum tCO 2 concentrations were available from 284 patients who transferred from ICHD to daily home HD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations